Gasoline, diesel, and ethanol biofuels from grasses and plants - Gupta, Ram B. (Cambridge University Press, 2010)
"This book introduces readers to second-generation biofuels obtained from non-food biomass, such as forest residue, agricultural residue, switch grass, and corn stover"--Provided by publisher